Ethnobotanical Study of Medicinal Plants in Karang Sidemen Village Lombok Central and Their Development as Biology Learning Material - Putri, Tasya Intania; Hadiprayitno, Gito; Handayani, Baiq Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Karang Sidemen Village is an area endowed with rich natural resources that can contribute to the sustainability of the local economy. One form of resource utilization that remains practiced by the community is the traditional use of medicinal plants, commonly referred to as ethnobotany, which has been transmitted across generations. Nevertheless, the continuity of this ethnobotanical knowledge is increasingly threatened due to the absence of systematic scientific documentation. Beyond its role in maintaining public health, ethnobotany also holds significant potential as a contextual learning resource in senior high school biology, particularly in biodiversity-related topics grounded in local wisdom. Consequently, efforts to preserve and incorporate this knowledge into the educational process are essential. This study was conducted to identify the types of medicinal plants utilized by the residents of Karang Sidemen Village and to transform the findings into biology teaching materials. A descriptive qualitative approach was applied, with data gathered through direct field observations and semi-structured interviews. The collected data were subsequently developed into instructional materials using the ADDIE model, limited to the stages of analysis, design, and development. The findings indicated that the community utilizes 45 medicinal plant species belonging to 19 different families. Various plant parts, including rhizomes, leaves, flowers, fruits, and seeds, are employed and processed using methods such as boiling, pounding, grating, and squeezing. These medicinal preparations are administered in multiple ways, including drinking, topical application, attachment, and dripping. The research output was a booklet designed as a biology learning medium, which underwent expert validation and was deemed appropriate for instructional use.